Evaluation of Efficacy of 3-Dimensional Delta Versus Trapezoidal Condylar Plates in Internal Fixation of Mandibular Subcondylar Fractures: A Clinical Study. Issue 1 (April 2019) - Lata, Jeevan; Verma, Nitin; Mahajan, Sarita
Abstract: Introduction: Among condylar fractures, surgical treatment is most commonly done for subcondylar fractures. Although 2 plate system is most commonly recommended, specially designed delta plate or trapezoidal condylar single 3-dimensional plate have been found to provide early functional rehabilitation with similar stability. Though studied in vitro, not much in vivo study has been done in clinical scenario. Aim and Objectives: Comparative assessment of functional and radiographic outcomes of patients who underwent subcondylar fracture fixation with trapezoidal and delta condylar plate. Methods: 20 patients presenting with subcondylar fracture requiring open reduction and internal fixation were included in this 2-year study from 2014 to 2016. Patients were randomly assigned to either one of the groups, with 10 being treated by each plate. Patients were evaluated regularly during 3 months follow-up on clinical parameters, such as occlusion, mouth opening, range of jaw movements, and radiologic parameters, such as fracture alignment, plate fracture, plate bending, screw loosening, secondary displacement of condylar fragment and its direction, ramus height, and any deviation. Results: In both groups, statistically significant improvement in occlusion seen from the third day to the third month ( P value = .04). Postoperative mouth opening, right and left lateral movements, and protrusive movements were statistically nonsignificant in both group A and group B. But within a group, improvements in the results were variable with regard to all these parameters at different intervals. Clinical and radiographic complications were nonsignificant in both group A and group B. Conclusion: This study is a preliminary effort to evaluate and compare different special plating systems in the management of condylar fractures with the new 3-dimensional trapezoidal and delta plating system, which gives excellent stability and rigidity. Improvement in occlusion was found to be gradual in both the plating system over a period of 3 months. Delta plate showed significant improvement in mouth opening at all intervals in comparison to Trapezoidal plate. Improvement in protrusive movement was found to be gradual and better with delta plate. A trapezoidal condylar plate holds goods for low subcondylar fractures owing to its wider dimension, though delta plate is versatile for both high and low subcondylar fracture.